The Changing Political Economy of Party Membership - PELIZZO, Riccardo (Institutional Knowledge at Singapore Management University, 2004)
A recent survey conducted in a sample of 83 countries by the Inter-Parliamentary Union in collaboration with the World Bank Institute on the “Relations between the Legislature and the Executive in the Context of Parliamentary Oversight” allows cross-national comparison for the role of legislatures in the budgetary process. One of the survey’s most significant indications is that legislatures in presidential systems are generally more involved in the preparation of the budget than legislatures in either parliamentary or semi-presidential systems. The picture, however, is very different when we look at legislatures’ oversight of the budget. Parliaments are generally more involved in the examination and final approval of the budget than are legislatures in presidential and semi-presidential systems1. In the light of these considerations, it should not be terribly surprising to find that the executive is more likely to be accountable to the legislature for its spending in parliamentary systems than in presidential systems.